Indicative supervision on the monetary business organizations (Banks) Case study: Iraq - داغر محمود (Journal of Economics and Administrative Sciences, 2012)
Indicative supervision represents the comparison between direct intervention (acquisition, nationalism) and participation through rules. The last financial crisis reflected our needs for different approaches of supervision consist with our goals, but the crisis reveals also number of sounds requested and pressured toward direct control (Intervention via forces) through government acquisition and nationalization. This study attempts to deal with crisis lessons, in the field of choice between indicative and direct supervision which government authorities used to reduce the bad effect on the monetary firms. Iraqi banks suffered from high levels of direct control from monetary authorities, so the changes and privatization on the new economic policy permit more and new banks’ activities. The study tries to test the reality and effectiveness of control through participation (seals) with comparison with direct governmental control. Below the paper structure: Introduction ( opposite solutions for the crises) Banking supervision; Macro- prudential supervision. Micro-prudential supervision. Business supervision. The financial reform. Macro – indication supervision. Case study: suggestion for Iraqi bank supervision. Bank structure. Central bank independency. Monitory policy assessment.